Meningkatkan Kompetensi Guru Fisika dengan Model STM “Two in One” Melalui Pelatihan dan Pengembangan Media Ajar Fisika Berbasis CMS (Content Management System), Web EXE dan Arduino di Kabupaten Purworejo - Umi Pratiwi; Sriyono Sriyono (Journal of Dedicators Community, 2018)
The purpose of this study is to provide training in making physics teaching media modules by utilizing WebExe CMS as well as training in making laboratory practice tools using Arduino microcontrollers and sensors. The problem faced by physics teachers at Puworejo today in designing web-based learning modules is the low understanding of the use of CMS learning applications. Partners in this study were physics teachers who were members of the Physics MGMP throughout Purworejo Regency, namely SMA N 1 Purworejo and SMA Muhammadiyh Purworejo. The research method used is training with the two in one STM (Sains Teknologi Masyarakat) model that integrates the provision of web-based teaching module training materials as well as training in the manufacture of practical tools based on the Arduino microcontroller. The results obtained that 50% of the training participants stated that the training was very useful and 90% stated that it would be carried out regularly. This training adds insight and ability to participants about IT-based media with e-learning material by 67% and arduino-based teaching media materials by 25%. It is expected that this training can improve the ability of participants in the development of further teaching media.